Geochemical, Mineralogical Properties and Industrial Applicability of Kaolin in Isan Ekiti, Nigeria - Olatunji K.J.,; Muhammed J.,; Olanrewaju D.M., (Advances in Engineering and Technology: An International Journal, 2023)
This study investigates geochemical and mineralogical property of kaolin in Isan Ekiti state, using X-Ray fluorescence and X-Ray diffractometer. The X – Ray Fluorescence of Samples is the major indicator, shows that the percentage Silicon oxide (SiO2) for both samples ranges from 50.35% to 49.76% with an average of 50.055%, Aluminum oxide (Al2O3) ranges from 24.02% to 27.25% with an average of 25.6%, Ferric Oxide (Fe2O3) ranges from 3.42% to 5.14%, with an average of 4.28%, Magnesium Oxide (MgO) ranges from 4.54% to 4.24% with an average of 4.38%, Calcium oxide from 0.67% to 0.63% with an average of 0.65%, and Potassium Oxide range from 3.97 to 2.47, with an average of 3.22%. The Results of X – Ray diffractometer for samples shows that Quartz has its peak at (34.65, 2.70, 2.01 and 2.75) 2Ө values for a sample while a sample was also identified at (32.57, 3.81, 2.23 and 1.65) 2Ө values. Kaolinite has its peak at (8.82, 4.13, 4.01, 2.84, 4.22, 4.52and 1.43) 2Ө values for a sample while another sample was also identified at (8.78,4.61, 4.42, 3.63, 6.29, 4.84 and 1.52) 2Ө values. The Anatase also has its at (4.76 and 2.32) 2Ө values for a sample while a sample was also identified at (3.64 and 3.75) 2Ө values. The Kaolinite in the samples ranges from 29.97% to 34.09% with an average of 32.03%, when compared with standard parameter, its suitable and can be used in coated paper, and when properly beneficiated, will be applicable in grades of ceramic production.